The Effectiveness of Using Nas Daily Youtube Videos in Enhanching Students’ Speaking Skills - Dwi Sulistyorini; Endang Susilowati; Haryani (Universitas An Nuur, 2023)
This study focuses on improving students' speaking ability through YouTube videos of Nas Daily channel, specifically the students (henceforth, the cadets) of Politeknik Bumi Akpelni studying in the fourth semester. There are many graduates in Marine Mechanical Engineering Technology (TRPK) who often receive comments from companies that there are still many TRPK cadets that are less active despite being in the world of work. The international level requires active English, especially during interviews and communication with seafarers from different countries on board. This study aims to explore the importance of using Nas's daily YouTube videos to boost students' speaking skills. This study employs an experimental design applying preliminary and predomination in each group. The population consists of fourth-semester interns and the sample is class TRPK A as the preliminary group and TRPK B as a predomination group consisting of 22 interns in each group. The first meeting is an advance-test for both groups. The researchers give the treatment during the second and third encounters, and so on. Nas daily YouTube videos are used for the preliminary group while the predomination group is treated with conventional methods. The last meeting was an end-test of the preliminary and predomination groups. The research tools used consists of conducting a simple dialogue with the subjects they have learned. Learners' speaking ability is assessed based on five aspects of speaking skills, namely articulation, grammar or morphology, vocabulary or the stock of words, chapters and fluency. The results show that the average advance-test scores for the preliminary and predomination groups are 48.60 and 44.26. End-test mean scores for the preliminary and predomination groups are 65.30 and 55.20. The average score of each of the 5 aspects of speaking also increased after using Nas Daily YouTube Videos for the preliminary group. The significance of this study is found by applying the t-test method. After carrying out the significance test, the t-count value (2.96) is higher than the t-table (1.76). This means that a significant difference in results between cadets’ speaking skills after being treated using the Nas Daily YouTube Video and using the conventional method of the fourth-semester cadets of Marine Mechanical Engineering Technology exists. This study concludes that cadets’ speaking skills improve well through activities using Nas Daily YouTube Video. They are more confident and have easy access anytime, anywhere to learn and to speak English. Besides, they also learn unique things from Nas' videos on YouTube.